2019
DOI: 10.1002/humu.23929
|View full text |Cite
|
Sign up to set email alerts
|

Clinical spectrum of individuals with pathogenic N F1 missense variants affecting p.Met1149, p.Arg1276, and p.Lys1423: genotype–phenotype study in neurofibromatosis type 1

Abstract: We report 281 individuals carrying a pathogenic recurrent NF1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
104
1
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 106 publications
(108 citation statements)
references
References 49 publications
2
104
1
1
Order By: Relevance
“…This is very hard to achieve, since a recent study using the largest NF1 gene variant database to date (8000 individuals) showed that a combination of the six most common recurrent missense or in-frame mutational hotspots (i.e., p.844-848, p.Met992del, p.Met1149, p.Arg1276, p.Lys1423, and p.Arg1809) represents only 4.8% of unrelated probands. 45 There are several clinical implications of our findings. First of all, we provide a robust confirmation that the chromosomal microdeletion genotype is associated with a lower cognitive ability compared with intragenic NF1 genotypes.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…This is very hard to achieve, since a recent study using the largest NF1 gene variant database to date (8000 individuals) showed that a combination of the six most common recurrent missense or in-frame mutational hotspots (i.e., p.844-848, p.Met992del, p.Met1149, p.Arg1276, p.Lys1423, and p.Arg1809) represents only 4.8% of unrelated probands. 45 There are several clinical implications of our findings. First of all, we provide a robust confirmation that the chromosomal microdeletion genotype is associated with a lower cognitive ability compared with intragenic NF1 genotypes.…”
Section: Discussionmentioning
confidence: 78%
“…Nevertheless, intragenic genotype-phenotype correlations concerning a single or a few neighboring amino acids (i.e., p.844-848, p.Met992del, p.Met1149, p.Arg1276, p.Lys1423, and p.Arg1809) have been identified in the context of somatic NF1 features. [26][27][28][29]45 While theoretically one would only need a sample size of n = 102 for a comparison of these six specific genotypes alongside a general group with other missense pathogenic variants (assuming a medium effect size of f 2 = 0.15, one categorical fixed effect with four categories, a significance criterion of α = 0.05, and a power of 1-β = 0.80), one would also need a reasonable number of individuals per group. As our data included only n = 2 p.844-848, n = 5 p.Met992del, n = 1 p.Met1149, n = 3 p.Arg1276, n = 4 p.Lys1423, and n = 9 p.Arg1809 individuals, we regarded our data as unsuitable for such an analysis.…”
Section: Discussionmentioning
confidence: 99%
“…These missense variants are more often associated with a Noonan syndrome‐like phenotype (Koczkowska et al., 2020).…”
Section: Genetic Counseling Processmentioning
confidence: 99%
“…NF1 gene has one of the highest spontaneous mutation rates and more than 3000 mutations have been recognized to date [68]. The following variants are associated with specific phenotypes: missense variants at the NF1 codons p.Arg1809, p.Met1149, p.Arg1276, and p.Lys1423 and the in-frame deletion c.2970-2972 delAAT [69][70][71]. In our series, 19 out of 35 patients underwent molecular testing for NF1 and an NF1 mutation was identified in 18 cases (Table 4).…”
Section: Discussionmentioning
confidence: 99%